Odpowiedź:
a)
[tex]\frac{2x + 3}{5} = \frac{2-x}{3} - x[/tex] / * 15
3(2x + 3) = 5(2-x) - 15x
6x + 9 = 10 - 10x - 15x
31x = 1
[tex]x = \frac{1}{31}[/tex]
b)
[tex]\frac{x + 1}{2} - \frac{x-1}{3} = \frac{1}{4}[/tex] / * 12
6(x + 1) - 4(x - 1) = 3
6x + 6 -4x + 1 = 3
2x = - 4
x = - 2
c)
[tex]\frac{4x + 7}{2} - \frac{5x - 1}{6} = x + 5[/tex] / * 6
3(4x + 7) - (5x - 1) = 6(x + 5)
12x + 21 - 5x + 1 = 6x + 30
13x = 8
[tex]x = \frac{8}{13}[/tex]
d)
[tex]\frac{x+5}{4} - \frac{2x + 1}{8} = \frac{1}{2}(2 - x)[/tex] / * 8
2(x + 5) - (2x + 1) = 4(2 - x)
2x + 10 - 2x - 1 = 8 - 4x
6x = - 1
[tex]x = -\frac{1}{6}[/tex]